PEMANFAATAN DAUN BANGUN-BANGUN UNTUK PENINGKATAN PRODUKSI SUSU KAMBING PERANAKAN ETTAWA PADA KELOMPOK WANITA TANI TALANG KUNING - Yurni Sari Amir; Nelzi Fati; Debby Syukriani; Irzal Irda; Toni Malvin (LPPM Universitas Andalas, 2021)
The Talang Kuning Women Farmers Group (KWT) is located in Nagari Batu Bulek, North Lintau Buo District, Tanah Datar Regency, West Sumatra. KWT Talang Kuning is engaged in raising Ettawa Peranakan goats. Fertile natural conditions and a large area of land support KWT for raising PE goats. The purpose of KWT for raising goats is to help the family's economy. The technology transfer carried out in KWT uses leaves as a feed additive in goat rations. It can be given directly in fresh condition, processed into an infusion or made into licking candy (saka mineral urea block). The infusion of the leaves of the wake was tested on lactating goats at KWT Talang Kuning. The method of implementing the activities is in the form of lectures and discussions and direct practice. The results of the trial on lactating PE goats showed an increase in milk production for two weeks. The provision of leaf plant seeds for KWTs developed on KWT land and the practice of leaf processing motivates KWTs in developing goats. Farmer groups very much need this activity to motivate their enthusiasm in advancing the livestock business. Group activities are usually technology transfer which is carried out by discussion and direct practice with them. Making infusion of the leaves of Bangun-bangun was very beneficial for the group because it was proven to increase milk production of lactating goats. To provide it sustainably, seeds that cuttings can plant have also been provided, and on the group's land, leaf plants have grown.